Oral dabigatran versus enoxaparin for thromboprophylaxis after primary total hip arthroplasty (RE-NOVATE II) - Eriksson, Bengt I.; Dahl, Ola E.; Huo, Michael H.; Kurth, Andreas A.; Hantel, Stefan; Hermansson, Karin; Schnee, Janet M.; Friedman, Richard J.; for the RE-NOVATE II Study Group (Thrombosis and Haemostasis, 2011)
This trial compared the efficacy and safety of oral dabigatran, a direct thrombin inhibitor, versus subcutaneous enoxaparin for extended thromboprophylaxis in patients undergoing total hip arthroplasty. A total of 2,055 patients were randomised to 28–35 days treatment with oral dabigatran, 220 mg once-daily, starting with a half-dose 1–4 hours after surgery, or subcutaneous enoxaparin 40 mg once-daily, starting the evening before surgery. The primary efficacy outcome was a composite of total venous thromboembolism [VTE] (venographic or symptomatic) and death from all-causes. The main secondary composite outcome was major VTE (proximal deep-vein thrombosis or non-fatal pulmonary embolism) plus VTE-related death. The main safety outcome was major bleeding. In total, 2,013 were treated, of whom 1,577 operated patients were included in the primary efficacy analysis. The primary efficacy outcome occurred in 7.7% of the dabigatran group versus 8.8% of the enoxaparin group, risk difference (RD) –1.1% (95%CI –3.8 to 1.6%); p<0.0001 for the pre-specified non-inferiority margin. Major VTE plus VTE-related death occurred in 2.2% of the dabigatran group versus 4.2% of the enoxaparin group, RD –1.9% (-3.6% to –0.2%); p=0.03. Major bleeding occurred in 1.4% of the dabigatran group and 0.9% of the enoxaparin group (p=0.40). The incidence of adverse events, including liver enzyme elevations and cardiac events, during treatment was similar between the groups. Extended prophylaxis with oral dabigatran 220 mg once-daily was as effective as sub-cutaneous enoxaparin 40 mg once-daily in reducing the risk of VTE after total hip arthroplasty, and superior to enoxaparin for reducing the risk of major VTE. The risk of bleeding and safety profiles were similar.
Keywords: Dabigatran etexilate; oral anticoagulant; total hip arthroplasty; prophylaxis; venous thromboembolism